2014
DOI: 10.1007/s00204-014-1382-8
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic-metabolizing enzymes in the skin of rat, mouse, pig, guinea pig, man, and in human skin models

Abstract: The exposure of the skin to medical drugs, skin care products, cosmetics, and other chemicals renders information on xenobiotic-metabolizing enzymes (XME) in the skin highly interesting. Since the use of freshly excised human skin for experimental investigations meets with ethical and practical limitations, information on XME in models comes in the focus including non-human mammalian species and in vitro skin models. This review attempts to summarize the information available in the open scientific literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 251 publications
(493 reference statements)
2
70
0
2
Order By: Relevance
“…It has been shown that cutaneous biotransformation can inactivate toxic agents; however, at the same time, biotransformation may also contribute to sensitization and genotoxicity. Comprehensive investigations into the expression and functionality of enzymes involved in cutaneous biotransformation of xenobiotics in human skin ex vivo as well as in reconstructed tissue models are ongoing, and knowledge continues to improve (Gotz et al, 2012;Huh et al, 2010;Oesch et al, 2014). Pre-validation studies have in fact been conducted with HSEs to address genotoxicity (Brinkmann et al, 2013;Fautz et al, 2013) and skin metabolism (Schafer-Korting et al, 2006).…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that cutaneous biotransformation can inactivate toxic agents; however, at the same time, biotransformation may also contribute to sensitization and genotoxicity. Comprehensive investigations into the expression and functionality of enzymes involved in cutaneous biotransformation of xenobiotics in human skin ex vivo as well as in reconstructed tissue models are ongoing, and knowledge continues to improve (Gotz et al, 2012;Huh et al, 2010;Oesch et al, 2014). Pre-validation studies have in fact been conducted with HSEs to address genotoxicity (Brinkmann et al, 2013;Fautz et al, 2013) and skin metabolism (Schafer-Korting et al, 2006).…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 99%
“…It has, however, to be noted that rat skin is more permeable than human skin (van Ravenzwaay and Leibold, 2004), and that skin metabolism differs between human and rat species. Thus, results obtained with rat models should be interpreted with care (Bartek et al, 1972;Jung and Maibach, 2015;Oesch et al, 2014). However, a triple pack using human in vitro data corrected by rat in vivo and in vitro data is an accepted refinement option for human risk assessment in the EU.…”
Section: General Introductionmentioning
confidence: 99%
“…Recently, Franz Oesch and colleagues have published a comprehensive review about the xenobiotic-metabolizing activity in skin of rat, mouse, pig, guinea pig, man, and human skin models (Oesch et al 2014). Since the skin is constantly exposed to different xenobiotics, its xenobiotic-metabolizing activity is of high relevance.…”
mentioning
confidence: 99%
“…The use of human skin is limited for ethical and practical reasons. Therefore, non-human skin and in vitro skin models are frequently applied (Oesch et al 2014). The authors give a comprehensive overview over possibilities and limitations of the most frequently applied in vitro systems used in skin toxicology.…”
mentioning
confidence: 99%
“…Drug metabolism represents a cutting edge topic in toxicology with a particular focus on toxification versus detoxification of xenobiotics (Oesch et al 2014;Rodriguez-Mateos et al 2014;Dohnal et al 2014), contribution of drug metabolism to oxidative stress (Xiao et al 2014;Møller et al 2014;Wu et al 2014), and regulation of metabolic activity (Juricek et al 2014;Bitter et al 2014;Lim et al 2014;Braeuning 2014). Moreover, recent research focuses on integrating metabolic pathways into mathematical models in order to predict the metabolic capacity of tissues and organs under physiological and disease conditions (Drasdo et al 2014a, b;Schliess et al 2014;Hoehme et al 2010).…”
mentioning
confidence: 99%